Effect of Varying Frequency of Fatigue Test on Durability of AISI 1045 Carbon Steel Plate Under Spectral Loading - Lukman Mohd Latifi,; Muhammad Muaz Mubasyir,; Shahrum Abdullah,; Salvinder Singh,; Karam Singh, (Penerbit Universiti Kebangsaan Malaysia, 2025)
In many practical applications, AISI 1045 carbon steel is subjected to various external factors, one of which is vibration. This vibration can induce resonance in the material, ultimately leading to fatigue due to cyclic stress. The aim of this study is to investigate the mechanical behavior of AISI 1045 carbon steel when subjected to both static and cyclic loading conditions, and to assess how its fatigue properties change across different test frequencies, and to validate a mathematical model that predicts fatigue life through statistical analysis. To ensure accurate and standardized testing, the specimen geometry follows the ASTM E466 standard for tensile and stress-life tests, and the ASTM E290 standard for three-point bending tests. The study involves conducting a series of mechanical tests, including tensile tests, stress-life tests, and three-point bending tests, which provide critical data on the material’s fatigue life under various conditions. By analyzing the results, the researchers aim to establish a clear relationship between the applied load frequency and the material’s fatigue life. Additionally, based on this relationship, they propose a mathematical model to predict the fatigue life of AISI 1045 carbon steel across different frequencies. This model could be useful in estimating the durability and performance of components made from this steel when subjected to dynamic and fluctuating loads, helping engineers design more reliable system and predicting material performance under varying operational conditions.